Randomized single-blind study to examine the implementation and effectiveness of integrating evidence-based early relational health programs in pediatrics for families with low incomes: A clinical trial protocol - Caitlin F. Canfield; Elizabeth B. Miller (PLoS ONE, 2026)
Disparities in early childhood development due to poverty are linked to lifelong gaps in health and well-being. To address such disparities, interventions must not only include the prevention of toxic stress, but also the promotion of early relational health—that is the presence of safe, stable, nurturing relationships between young children and their caregivers. Moreover, a public health approach that integrates multiple programs in order to meet the unique needs and build on the varied resources of individual families is needed to effect population-level change. This randomized controlled trial seeks to examine the implementation and effectiveness of combining two evidence-based interventions, HealthySteps and PlayReadVIP. A total of 355 parent-child dyads, 35 in the implementation phase and 320 in the effectiveness phase, will be randomly assigned to receive HealthySteps+PlayReadVIP or traditional HealthySteps, as an active Control. Families will receive the intervention at each pediatric well-child visit from birth to age 2 and will complete assessments at enrollment and child age 12 and 24 months. In addition, up to ten HealthySteps Specialists and other care providers will be enrolled and will complete surveys at each assessment point. The primary outcomes include positive parent-child relationship, parent cognitive stimulation, and child socioemotional development.